2022
DOI: 10.3389/frsen.2022.934608
|View full text |Cite
|
Sign up to set email alerts
|

Dolphin communication during widespread systematic noise reduction-a natural experiment amid COVID-19 lockdowns

Abstract: Underwater noise from human activities is recognized as a world-wide problem, with important repercussions on the acoustic communication of aquatic mammals. During the COVID-19 pandemic, the government of Panama went into a nationwide lockdown to limit the spread of the virus. This lockdown resulted in the closing of tourism infrastructure and limited mobility in both land and coastal areas. We used this “natural experiment” as an opportunity to study the impact of tour-boat activities on dolphin communication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 66 publications
(93 reference statements)
0
5
0
Order By: Relevance
“…It is necessary to regulate and control boat traffic. Significant changes in dolphin habitat, such as in the western portion of Panama's Dolphin Bay, might result from a shift in boat traffic activities (Gagne et al., 2022 ). The echolocation signals of Yangtze finless porpoise are distinguished by their narrow‐band characteristics (with a 3 dB bandwidth of approximately 22 kHz) and high frequencies (with a peak frequency around 129 kHz).…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to regulate and control boat traffic. Significant changes in dolphin habitat, such as in the western portion of Panama's Dolphin Bay, might result from a shift in boat traffic activities (Gagne et al., 2022 ). The echolocation signals of Yangtze finless porpoise are distinguished by their narrow‐band characteristics (with a 3 dB bandwidth of approximately 22 kHz) and high frequencies (with a peak frequency around 129 kHz).…”
Section: Discussionmentioning
confidence: 99%
“…Table S3 ). Overall, dolphins show a great degree of plasticity in their whistle frequency range, which allows them to quickly respond to changes in their acoustic environments 5 , 49 , 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggests that offshore dolphins have a greater use of frequency modulated contours than coastal dolphins, and we are interested in determining if other offshore pantropical spotted dolphin populations show similar levels of modulation. Frequency modulation patterns in dolphins can serve for species identification 16 , 64 , carry information about individual identity 65 , express emotional state during social interactions 5 , 66 , and vary with different acoustic environments 8 , 49 . Therefore, the observed differences in the proportion of modulated whistles in the repertoire of coastal and offshore dolphins could indicate population-specific differences in group size, social dynamics, and habitat specialization.…”
Section: Discussionmentioning
confidence: 99%
“…In Hawaiʻi, the potential delay in the rebound period, as exhibited in the Hawaiʻi island vessel data, was likely due to the extended shut-down periods and strict travel restrictions imposed by the State of Hawaiʻi that lasted until summer 2021. Globally, the effects of COVID-19 are thought to have increased the communication range for some marine mammals (Pine et al, 2021), which led to an increase in humpback whale calling (Laute et al, 2022) and an increase in the detection of delphinid whistles (Gagne et al, 2022). Laute et al (2022) found that the decrease in whale watch vessels in Iceland during the pandemic correlated with an increase in the humpback whale calling rate on the foraging ground.…”
Section: Covid-19 Implicationsmentioning
confidence: 99%